3 UMPSA PASKAM Second Lieutenants receive Best Cadet Award Series 1/2023 - Naqiah, Puaad (UMPSA, 2025)
GAMBANG, 9 August 2025 – Three Second Lieutenants of the Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Maritime Cadet Corps (PASKAM) created personal history when they were named recipients of the PASKAM Best Cadet Award Series 1/2023 at the PASKAM UMPSA Second Lieutenant Commissioning and Graduation Ceremony held at Dewan Astaka, Gambang Campus recently.